Multivariate analysis of variations in intrinsic foot musculature among hominoids. Issue 5 (12th January 2018) - Oishi, Motoharu; Ogihara, Naomichi; Shimizu, Daisuke; Kikuchi, Yasuhiro; Endo, Hideki; Une, Yumi; Soeta, Satoshi; Amasaki, Hajime; Ichihara, Nobutsune
Abstract: Comparative analysis of the foot muscle architecture among extant great apes is important for understanding the evolution of the human foot and, hence, human habitual bipedal walking. However, to our knowledge, there is no previous report of a quantitative comparison of hominoid intrinsic foot muscle dimensions. In the present study, we quantitatively compared muscle dimensions of the hominoid foot by means of multivariate analysis. The foot muscle mass and physiological cross‐sectional area (PCSA) of five chimpanzees, one bonobo, two gorillas, and six orangutans were obtained by our own dissections, and those of humans were taken from published accounts. The muscle mass and PCSA were respectively divided by the total mass and total PCSA of the intrinsic muscles of the entire foot for normalization. Variations in muscle architecture among human and extant great apes were quantified based on principal component analysis. Our results demonstrated that the muscle architecture of the orangutan was the most distinctive, having a larger first dorsal interosseous muscle and smaller abductor hallucis brevis muscle. On the other hand, the gorilla was found to be unique in having a larger abductor digiti minimi muscle. Humans were distinguished from extant great apes by a larger quadratus plantae muscle. The chimpanzee and the bonobo appeared to have very similar muscle architecture, with an intermediate position between the human and the orangutan. These differences (or similarities) in architecture of the intrinsic foot muscles among humans and great apes correspond well to the differences in phylogeny, positional behavior, and locomotion.